Padrões emergentes em encontros consonantais heterossilábicos - Carolina Gabriele Lima Moreira (2022)
This dissertation’s goal is the study of emerging patterns in heterossyllabic consonant clusters in Belo Horizonte’s Brazilian Portuguese. Heterossyllabic consonant clusters are present in words such as vista [visˈtə], in which the consonants [s] and [t] form a heterossyllabic consonant cluster. As reported by previous works, the second consonant from the cluster may undergo lenition (CRISTÓFARO SILVA, 2000, OLIVEIRA GUIMARÃES, 2004, CRISTÓFARO SILVA; OLIVEIRA GUIMARÃES, 2004, 2009, RABELO, 2010, CARVALHO, 2015). A word such as vestido [visˈtʃidʊ]~[ viʃˈtʃidʊ] may be manifested as [viˈʃidʊ]. This dissertation focuses on the following consonant clusters: (alveolar sibilant + alveolar plosive), (alveolar sibilant + alveopalatal affricate) and (alveolar sibilant + labiodental fricative) – [st], [zd], [stʃ], [zdʒ], [sf] e [zv]. The objectives of this dissertation included addressing this phenomenon with an experimental approach, quantify the lenition cases, identify the segmental reduction in different consonant clusters, investigate the phenomenon in the post lexical context, analyze the phenomenon acoustically and discuss how phonological theory models can explain this case of lenition. The theoretical reference used was Exemplar Theory and the methodological reference used was Laboratory Phonology. The data for the study was colleted through a voice recording experiment with residents of the city of Belo Horizonte. The results indicated that the lenition in heterossyllabic consonant clusters is an active phonological phenomenon in Belo Horizonte’s Brazilian Portuguese. The clusters [stʃ] and [zdʒ] clusters showed the highest amount of lenition cases. The results also showed that the phenomenon is active, not only lexically, but post lexically as well. Therefore, this dissertation analyzed the lenition in heterossyllabic consonant clusters in Brazilian Portuguese with an experimental approach. This research offers as contributions to the literature about this phenomenon: an expansion of the consonant clusters addressed in detail, a carefully conducted acoustic analysis and the analysis of a context that hasn’t been addressed in research before, the post lexical context.